2014
DOI: 10.1016/j.jconrel.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

RNAi-mediated gene knockdown and anti-angiogenic therapy of RCCs using a cyclic RGD-modified liposomal-siRNA system

Abstract: Angiogenesis is one of crucial processes associated with tumor growth and development, and consequently a prime target for cancer therapy. Although tumor endothelial cells (TECs) play a key role in pathological angiogenesis, investigating phenotypical changes in neovessels when a gene expression in TEC is suppressed is a difficult task. Small interfering RNA (siRNA) represents a potential agent due to its ability to silence a gene of interest. We previously developed a system for in vivo siRNA delivery to canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
86
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(87 citation statements)
references
References 44 publications
1
86
0
Order By: Relevance
“…The increased expression of α V β 3 integrin on tumor endothelial cells was exploited for delivery of siRNA through a cationic lipid system with cyclic RGD grafted onto its surface [128]. In vitro, the integrin presence was essential for successful uptake and gene silencing, and in vivo, the targeted system resulted in siRNA-mediated gene silencing in tumor endothelial cells, but not in other endothelia.…”
Section: Targets and Ligands For Leukocytes And Endotheliummentioning
confidence: 99%
“…The increased expression of α V β 3 integrin on tumor endothelial cells was exploited for delivery of siRNA through a cationic lipid system with cyclic RGD grafted onto its surface [128]. In vitro, the integrin presence was essential for successful uptake and gene silencing, and in vivo, the targeted system resulted in siRNA-mediated gene silencing in tumor endothelial cells, but not in other endothelia.…”
Section: Targets and Ligands For Leukocytes And Endotheliummentioning
confidence: 99%
“…Thus, the prepared RGD-MEND was able to deliver siRNA specifically to TECs. 15 When the LNPs were fluorescently labeled, a lipophilic dye, DiI or DiD was added to the lipid mixture prior to the first dilution. The recovery rate and encapsulation efficiency of siRNA were determined by RiboGreen.…”
Section: Methodsmentioning
confidence: 99%
“…We previously confirmed that an RGD-MEND encapsulating si-VR2 caused a delay in tumor growth by decreasing the density of microvessels in tumor tissue. 15 On the other hand, a continuous treatment (3 separate injections of the RGD-MEND was started prior to the first injection of DOX-LNP) and the results indicated a more moderate therapeutic effect (not data shown). This can be attributed to short-lived silencing by the RGD-MEND (< 72 hours).…”
Section: Vegfr2 Knockdown and Consequent Changes Of Intratumoral Distmentioning
confidence: 97%
See 1 more Smart Citation
“…7) The YSK-MEND effectively delivered siRNA to the liver, 8) tumors 9) and tumor endothelial cells. 10) This type of YSK-MEND would also be predicted to have potential for pDNA delivery.…”
mentioning
confidence: 99%